Transplant eligibility in elderly multiple myeloma patients: Prospective external validation of the international myeloma working group frailty score and comparison with clinical judgment and other comorbidity scores in unselected patients aged 65‐75 years. Issue 7 (23rd April 2020) - Belotti, Angelo; Ribolla, Rossella; Cancelli, Valeria; Crippa, Claudia; Bianchetti, Nicola; Ferrari, Samantha; Bottelli, Chiara; Cattaneo, Chiara; Tucci, Alessandra; De La Fuente Barrigon, Carmen; Rossi, Giuseppe
Abstract: Autologous stem cell transplantation (ASCT) is feasible and effective in selected older patients with Multiple Myeloma, but specific criteria for evaluating ASCT eligibility in elderly patients are lacking. We evaluated 131 patients aged 65‐75 considered for ASCT at our center: The Charlson Comorbidity Index (CCI), Hematopoietic cell transplantation comorbidity index (HCT‐CI) and IMWG frailty score were obtained at diagnosis, but the intensity of treatment was left to physician's choice. The scores and age's impact on outcome was analyzed: 85 patients were judged transplant eligible, whereas 46 patients received a less intensive treatment (median follow up 27 months). No patients classified as frail had been considered eligible to ASCT with a worse outcome compared to fit and unfit patients (median PFS (progression free survival): 7.9 vs 32.9 and 29.6 months; P < .001). PFS was superior in the ASCT group (35.6 vs 19.9 months, P .013). In the ASCT group, PFS was better in patients aged 65‐69 years than in patients ≥70 (51.5 vs 27.7 months, P .004). Indeed, in unfit patients aged ≥70 the PFS of the ASCT group was comparable to NO ASCT group (18 vs 27 months, P = .33) whereas in unfit patients aged 65‐69 PFS was superior in the ASCT group: 43.3 vs 18.4 months, P .01. ISS III and impaired functional status independently affected PFS in a multivariate analysis ( P .011 and P .006). While CCI and HCT‐CI did not predict different outcome in ASCT patients, the IMWG frailty score would be of help in identifying unfit patients aged 70‐75, whose outcome with ASCT selected by clinical judgment was no better than with less intensive treatments.